Cytotoxiciy of Naja nubiae (Serpentes: Elapidae) and Echis ocellatus (Serpentes: Viperidae) Venoms from Sudan. (15th March 2015) - Khalid, Huda; Mukhtar, Maowia Mohammed; Konstantakopoulos, Nicki
Abstract : In Sudan, as in many African countries, no local specific antivenom is manufactured resulting in snake bite victims being treated by antivenoms imported from abroad. In the present work we measured the cytotoxic effect of the recently described spitting cobra ( Naja nubiae ) and the carpet viper ( Echis ocellatus ) snake venoms using a cell based assay. We also investigated the efficacy of four antivenoms CSL (Australia), SAIMR (South Africa), snake venom antiserum (India), and EchiTAb-Plus-ICP (Cost Rica) to neutralize the cytotoxic effect of the two venoms. The venoms resulted in a remarkable inhibition of cell viability with N. nubiae being more cytotoxic than E. ocellatus . The four antivenoms studied were effective in neutralizing N. nubiae cytotoxicity. However, only partial efficacy in neutralizing the cytotoxic effect of E. ocellatus was achieved using CSL (Australia) and SVA (India) antivenoms. Based on the cross neutralization by the four antivenoms, the Sudanese N. nubiae venom most likely has homologous epitopes with similar snakes from Australia, South Africa, India, and Cost Rica, while E. ocellatus venom from Sudan shares little homology with similar snakes from other countries.